Eermaili as living Islam: ritual practice and religious transmission among the Hui Muslims in China - Mai, Jianjun; Min, Keqin (UniSZA, 2025)
This article examines Hui Ermaili as a form of “living Islam”—a ritual practice that integrates theological intentionality, communal devotion, and embodied transmission of Islamic knowledge within China’s minority Hui Muslim context. Ermaili, derived from the Arabic term ʿamal (righteous deed), encompasses Qur’anic recitation, prophetic eulogy chanting, supplication, charity, sermons, and communal meals. Far from being a syncretic or folkloric tradition, Ermaili is framed here as daʿwah bi’l-ḥāl: a performative invitation to Islam through lived example rather than verbal preaching. Drawing on Talal Asad's concept of discursive tradition and Catherine Bell's theory of ritualisation, the study interprets Ermaili because of religious agency through which Islamic knowledge and values are transmitted across generations, Islamic faith is strengthened, and communal solidarity is reinforced. Methodologically, the research combines insider ethnography with textual analysis and comparative ritual studies. The author approaches the topic as both researcher and participant-observer, drawing on experience as a Hui Muslim raised within the Ermaili tradition. The article challenges reductionist readings that treat Ermaili as cultural adaptation, arguing instead for its theological authenticity through examination of Sufi genealogies and scriptural foundations. Despite reformist critiques from movements like Yihewani that view certain Ermaili practices as bidʿah (innovation), the study demonstrates Ermaili's persistence as authentic Islamic devotion. By foregrounding Ermaili’s pedagogical, ethical, and spiritual dimensions, the study contributes to broader discussions in the anthropology of Islam, minority daʿwah, and ritual theory. It affirms Ermaili as a vital expression of living Islam – where belief is enacted, theology embodied, and religious agency cultivated in everyday life